Kerukunan Umat Beragama di Provinsi Nusa Tenggara Timur (NTT) - Ahmad Sodli (Analisa: Journal of Social Science and Religion, 2009)
Current research focused on regligious community reconsiliation / harmonybetween Islam and Christian communities (8 locations), Islam and Catholiccommunities (1 location), and Christian dan Catholic communities (1 location). Theresearch aimed to describe relationship between those religious communities coveringcooperations, competitions, conflicts, and their resolutions, and other supportingfactors. The research used qualitative approach with in-dept interviews, observationsand documents / literature reviews as the technic for collecting data. Cooperation covered relgious places building, religious celebration / festives, andnew year celebration. Supporting factors are governmental advices, religious leadersand religious guidances. Competition are shown in religious places, economic activitiesand religious spreads. Conficts happen in using loudspeakers and wandering pets /animals. Conflict resolution is by conference.Key Words: Relationship, Islam, Christian, Catholic, NTT